The Influence of Banking Risks on the Health Level of Commercial Banks Listed on the Indonesia Stock Exchange from 2017 to 2022 - Primaditya, Calvin Yusuf; Purwanto, Agus (Diponegoro Journal of Accounting, 2024)
This research aims to test and analyze empirical evidence regarding the influence of credit risk, market risk, liquidity risk, and operational risk on the health level of banks. The dependent variable in this study is the health level of banks, which is measured based on self-assessment ratings at each bank. The independent variables in the study are credit risk, measured by NPL (Non-Performing Loans), market risk, measured by NIM (Net Interest Margin), liquidity risk, measured by LDR (Loan to Deposit Ratio), and operational risk, measured by BOPO (Operational Cost to Operational Income Ratio). The population in this research consists of all commercial banks listed on the Indonesian Stock Exchange during the period 2017 – 2022. The sample determination in this study uses a purposive sampling technique with specific criteria. The total sample in the study consists of 45 commercial banks listed on the Indonesian Stock Exchange during the period 2017 – 2022. The analysis method used in the research is the ordinal logistic regression model. The results of the analysis indicate that credit risk, market risk, and operational risk have a significant negative impact on the health level of banks. Additionally, liquidity risk does not have a significant impact on the health level of banks.